Technological Bases of The Process of Organizing Literature Lessons - Amanliqova Nafisa Rakhmatullaevna (International Journal on Orange Technologies, 2021)
This article describes a number of didactic principles and laws in the design and organization of literature lessons, ie defining the main purpose of the lesson, designing the lesson, developing its model, identifying the main ways to achieve the goal, engaging students in reading, engaging them in this activity. and explanatory work.